EFEKTIVITAS MADU DAN TABLET Fe SEBAGAI UPAYA PENINGKATAN KADAR HEMOGLOBIN PADA REMAJA PUTRI DI PONDOK PESANTREN - Damayanti, Dini Fitri; Astuti, Wahyu; Wati, Ellisa; Marsita, Elma (Journal of Nutrition College, 2021)
Background: Anemia is a condition in which the levels of hemoglobin, hematocrit and red blood cells are lower than normal values. Women have the highest risk of developing anemia, especially in young women. The prevalence rate of anemia in Indonesia, namely in adolescent women is 26.50%. Anemia in adolescents can decreased concentration of learning, frequent fatigue, drowsiness, lower body resistance, complications in pregnancy and childbirth when a future mother. The government make a policy to overcome the problem of anemia due to iron deficiency by provision of iron supplements. Objectives: Analyze effectiveness of honey and iron supplementation to help increase the levels of hemoglobin in adolescent girl on boarding school Hidayatul Muslim Kubu Raya. Methods: This type of research is experimental pre-test and post-test with control group design. The sample of this study was young women at the Hidayatul Muslimin Islamic Boarding School in Kubu Raya aged 16-19 years, totaling 36 people with exclusion criteria (18 samples of the intervention group and 18 samples of the control group). The sampling technique was purposive sampling and the method of analysis used paired t-test and independent t-test. Results: Based on the statistic test, there was a significant difference between giving honey with iron supplementation and only iron supplementation to increase hemoglobin levels in adolescent girls (p=0.002).Conclusion: Honey with iron supplementation was effective to helped increase the levels of hemoglobin in adolescent girl on boarding school Hidayatul Muslimin Kubu Raya.